Pre-transplant donor specific antibodies in ABO incompatible kidney transplantation – data from the Swiss transplant cohort study - Deng, Yun; Frischnknecht, Lukas; Wehmeier, Caroline; de Rougemont, Olivier; Villard, Jean; Ferrari-Lacraz, Sylvie; Golshayan, Déla; Gannagé, Monique; Binet, Isabelle; Wirthmueller, Urs; Sidler, Daniel; Schachtner, Thomas; et al. (Frontiers in Immunology, 2024)
Background: Living donor (LD) kidney transplantation in the setting of ABO blood group incompatibility (ABOi) has been previously reported to be associated with increased risk for antibodymediated rejection (ABMR). It is however unclear if the presence of pre-transplant donor specific antibodies (DSA) works as an additive risk factor in the setting of ABOi and if DSA positive ABOi transplants have a significantly worse long-term outcome as compared with ABO compatible (ABOc) DSA positive transplants.We investigated the effect of pre-transplant DSA in the ABOi and ABOc setting on the risk of antibody-mediated rejection (ABMR) and graft loss in a cohort of 952 LD kidney transplants. Results: We found a higher incidence of ABMR in ABOi transplants as compared to ABOc transplants but this did not significantly affect graft survival or overall survival which was similar in both groups. The presence of pre-transplant DSA was associated with a significantly increased risk of ABMR and graft loss both in the ABOi and ABOc setting. We could not detect an additional risk of DSA in the ABOi setting and outcomes were comparable between DSA positive ABOi and ABOc recipients. Furthermore, a combination of DSA directed at both Class I and Class II, as well as DSA with a high mean fluorescence intensity (MFI) showed the strongest relation to ABMR development and graft loss.The presence of pre-transplant DSA was associated with a significantly worse long-term outcome in both ABOi and ABOc LD kidney transplants and our results suggests that the risk associated with pre-transplant DSA is perhaps not augmented in the ABOi setting. Conclusions: Our study is the first to investigate the long-term effects of DSA in the ABOi setting and argues that pre-transplant DSA risk could potentially be evaluated similarly regardless of ABO compatibility status.